(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The discovery in Ruscino in 2004 of two texts written in Iberian script on lead tablets is an important contribution and a starting point to re-examine the epigraphic documentation of the site. The material of the Iberian graffiti, mostly on local ceramicsbetter known today by the excavations and recent studies, demonstrate the common use of writing for at least part of theoppidum population. The two lead strips were associated each other and perhaps were written by the same hand, the writing system does not seem to be dual and the palaeography could be between 250 and 150 BC. The texts show Iberian onomastic elements but not Gaulish, perhaps place names and some lexical indication of its economic character.